Deskripsi Pengelolaan Pendidikan Karakter Di sekolah Menengah Pertama Al Muslim Tambun - Isep Djuanda (Alim | Journal of Islamic Education, 2020)
This study is aimed to figure out character education management in SMP Al Muslim Tambun and to uncover the obstacles in managing character education in SMP Al Muslim. The research design used is qualitative research design which describes the management of character education. The data collection technique employed are observation, interview, and documentary study. Data analytical technique used in this research are qualitative descriptive which will be applied as the approach to describe the result of observation, interview and documentary study. The research results show us that 1) character education management in SMP Al Muslim Tambun is conducted through school management, learning activities, as well as habitual/coaching activities; 2) the obstacles in managing character education in SMP Al Muslim Tambun are caused by internal and external factors. Internal factors include students and teachers/employees. Meanwhile, the external factors come from parents, shuttle service and foundation.